Interlaboratory comparison of particle filtration efficiency testing equipment. - Sipkens, Timothy A.; Mehri, Rym; Perez Calderon, Ruth; Green, Richard G.; Oldershaw, Andrew; Smallwood, Gregory J. (Journal of Occupational & Environmental Hygiene, 2025)
Particle filtration efficiency (PFE) is a critical property of face masks, with the most common test methods using sodium chloride as a challenge aerosol. In the absence of bottom-up uncertainty budgets for PFE, interlaboratory comparisons provide an alternative route to robustly quantify the precision and bias of the method. This work presents the results of several interlaboratory comparisons of particle filtration efficiency performed across a network of laboratories. Using log-penetration as a surrogate for PFE, it is shown that expanded reproducibility intervals were consistent across most samples, at around 26% of the nominal value of log-penetration. Between-laboratory contributions to this reproducibility were significant, nearly doubling the lab-reported uncertainties in most instances and emphasizing the need for ongoing interlaboratory studies to be performed for particle filtration. More work is required to identify the causes of these between-laboratory differences, requiring dedicated testing. Alongside uncertainty quantification, testing materials across a range of variables (such as the number of layers, amount of charge on the material, and basis weight) affirm that constant quality is a good approximation when layering or changing the basis weight on an otherwise identical material.